ClimMob, a digital platform for large-N on-farm experimentation with climate adaptation options - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Scaling is ongoing during 2018 by ISSD-Ethiopia, who will reach over 100,000 accumulatively in a direct way (involvement in trials) and generating variety recommendations for several millions of farmers.